Implementation of Infant Massage Therapy to Increase Oxygen Saturation in Neonates: A Scoping Review - Jubaedah, Dede; Fitri, Siti Yuyun Rahayu Yuyun; Mardhiyah, Ai (GLOBAL HEALTH SCIENCE GROUP, 2024)
Stress and pain in premature babies can cause a decrease in oxygen saturation and changes in respiratory rate. Touch stimulation is one of the most advanced senses used by medical practitioners to soothe babies. Objective: This review aims to see the effectiveness of implementing infant massage therapy in increasing oxygen saturation in neonates. Method: A literature search was conducted on: PubMed, ScienceDirect, and CINAHL. The collected data is then extracted, synthesized, and presented as tables and narratives. The search strategy uses the keywords (